2003
DOI: 10.1007/s00441-003-0702-8
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of type II collagen biosynthesis and secretion in bovine chondrocytes cultured with degraded collagen

Abstract: The functional integrity of articular cartilage is dependent on the maintenance of the extracellular matrix (ECM), a process which is controlled by chondrocytes. The regulation of ECM biosynthesis is complex and a variety of substances have been found to influence chondrocyte metabolism. In the present study we have investigated the effect of degraded collagen on the formation of type II collagen by mature bovine chondrocytes in a cell culture model. The culture medium was supplemented with collagen hydrolysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 22 publications
4
92
1
4
Order By: Relevance
“…Interestingly, chondrocyte populations were not only preserved, but the number of cells actively producing Safranin O stained proteoglycan matrix was increased significantly in the hCol1-treated groups at both time points. These results parallel published work suggesting chondrogenic and cartilage matrix anabolic effects of hCol1 in adipose tissue derived stem cells [19], and the anabolic effects of type 1 collagen hydrolysate and prolyl-hydroxyproline [55, 56] and collagen peptide fragments [57] on chondrocyte matrix production.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, chondrocyte populations were not only preserved, but the number of cells actively producing Safranin O stained proteoglycan matrix was increased significantly in the hCol1-treated groups at both time points. These results parallel published work suggesting chondrogenic and cartilage matrix anabolic effects of hCol1 in adipose tissue derived stem cells [19], and the anabolic effects of type 1 collagen hydrolysate and prolyl-hydroxyproline [55, 56] and collagen peptide fragments [57] on chondrocyte matrix production.…”
Section: Discussionsupporting
confidence: 88%
“…Another study performed in rats provides autoradiographic evidence for the presence of radiolabeled proline-hydroxyproline dipeptide in articular cartilage and synovium within 30 minutes of ingestion [64]. As mentioned earlier in this report, there are also in vitro data indicating that various types of collagen peptides can directly affect chondrocyte function [19, 45, 55, 57], supporting the hypothesis that absorbed collagen peptide fragments could directly influence cell behavior in the joint. While this line of reasoning lays out a basis for orally ingested collagen peptides or cartilage matrix molecules to impact joint tissues, the nature of the peptides/compounds that actually make it to the joint is not known, and the pathway of action, whether it be in the chondrocyte, synoviocyte, or other cell in the joint, can only be speculated.…”
Section: Discussionsupporting
confidence: 79%
“…After 21 days, these cells secreted matrix with high proteoglycan content which stained positive for toluidine blue (Figure 2H) and collagen type II (COL II) (Figure 2J) and formed calcified nodules (Figure 2K), indicating that these cells form cartilage matrix [36]. RT-PCR demonstrated that treated cells in chondrogenic media expressed Sox9 and increased expression of collagen type II ( Col2a1 ) genes which are specific markers for chondrocyte differentiation [37].…”
Section: Resultsmentioning
confidence: 99%
“…The primary assays will characterize antibodies associated with immunohistochemistry and histochemical staining to include the following:

Type II Collagen as the predominant collagen in healthy articular cartilage. Type II collagen forms a three-dimensional fibrillar network essential for the tensile stiffness and strength of cartilage [32].

Aggrecan as the third major component of articular cartilage, constituting the majority of the proteoglycanhyaluronic acid polymers.

…”
Section: Engineering and Experimental Design Methodsmentioning
confidence: 99%
“…During tissue turnover aggrecan and its fragments originating from the core protein part of aggrecan are released into the supernatant of cartilage explant cultures. The total aggrecan can be identified via an enzyme-immunoassay for the quantitative determination of aggrecan and its fragments containing the G1 and/or G2 domains that are released into the supernatant from articular cartilage explants [32]. …”
Section: Engineering and Experimental Design Methodsmentioning
confidence: 99%